Investigating Literacy Practices in a University EFL Context from Multiliteracies and Multimodal Perspective A Case Study - Nabhan Salim; Hidayat Rahmad (2018)
This study attempts to investigate the literacy practices of EFL teaching and learning in higher education level from multiliteracies and multimodal perspective. Mixed methods were used: questionaires to the students, interviews with both teachers and students, focus group discussion with students, observation, and documents. The study was focused on the English reading and writing classroom activities. The results of the study revealed that most participating students frequently utilized on screen text and digital devices instead of printed paper in their reading and writing activities. In addition, despite the fact that teachers still used print-based literacy, they supported the adoption of digital and multimodal literacy in their teaching. The findings also indicated that there was mostly misconception of English literacy skills limited to the only targeted skills of English language, and yet the nature of reading and writing practices has developed towards incorportion of printed based texts with multimodal texts. Nevertheless, some challenges occured in integrating multimodality into practices including curriculum design and different learners’ qualification. Findings collected from the this study might have implications for the curriculum development within the framework of multiliteracies and multimodality in the contemporary teaching and learning English language particularly in response to the emergence of technology.
Keywords: Oktatástudomány